2014
DOI: 10.1371/journal.pone.0104311
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis of Functional Single Nucleotide Polymorphisms Associated with the CYP11B2 Gene

Abstract: Single nucleotide polymorphisms (SNPs) are the most common type of genetic variations in humans and play a major role in the genetics of human phenotype variation and the genetic basis of human complex diseases. Recently, there is considerable interest in understanding the possible role of the CYP11B2 gene with corticosterone methyl oxidase deficiency, primary aldosteronism, and cardio-cerebro-vascular diseases. Hence, the elucidation of the function and molecular dynamic behavior of CYP11B2 mutations is cruci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 48 publications
0
30
0
1
Order By: Relevance
“…Bayesian calculation method was used to calculate conservation score from protein sequence (49, 50). A conservation score between 1 and 4 was indicated as variable, whereas a score of 5–6 was intermediate, and a score between 7 to 9 indicated as conserved (51).…”
Section: Methodologiesmentioning
confidence: 99%
“…Bayesian calculation method was used to calculate conservation score from protein sequence (49, 50). A conservation score between 1 and 4 was indicated as variable, whereas a score of 5–6 was intermediate, and a score between 7 to 9 indicated as conserved (51).…”
Section: Methodologiesmentioning
confidence: 99%
“…The query was submitted in the form of SNP IDs or as protein sequences. The underlying principle of this program is that SIFT takes a query sequence and uses multiple alignment information to predict tolerated and deleterious substitutions for every position of the query sequence (Jia et al 2014). The cutoff value in the SIFT program is a tolerance index of C0.05.…”
Section: Establishing Deleterious Nssnps By Sift and Predictsnpmentioning
confidence: 99%
“…Brand E, et. Al., found a positive association of CYP11B2-344T allele with essential hypertension [89]. During a study, 175 cardiac patients of European Continental Ancestry Population were diagonosed and it was identified that C allele (CT, CC) at −344T/C SNP position in “aldosterone synthase” gene does not considerably effect clinical prognosis of cardiac heart-failure [7].…”
Section: Introductionmentioning
confidence: 99%
“…Jia et.al [9] studied CYP11B2 gene for 52 SNPs and found four SNPs as deleterious. The novelty of this study was that we filtered out 29 deleterious SNPs from a large number of non-risk alleles and studied the effect of Fadrozole drug over some pathogenic SNPs.…”
Section: Introductionmentioning
confidence: 99%